Continuous-flow synthesis of MIL-53(Cr) with a polar linker: probing the nanoscale piezoelectric effect. Issue 24 (16th June 2021) - Xue, Feifei; Cao, Jian; Li, Xiaoting; Feng, Jingjing; Tao, Minli; Xue, Bin
Abstract : MIL-53(Cr) MOF material was designed and prepared with polar linker including fluorine group. The MIL-53(Cr)-F nanoparticles can be fabricated by continuous flow method at large scale, and these materials display nanoscale piezo-responses. Abstract : Polar metal–organic frameworks (MOFs) have potential applications due to the fact that their organic linkers can be conveniently modified, which endows them with different properties such as non-linear optical, piezoelectric, pyroelectric, and ferroelectric performance. In the present study, an MIL-53(Cr) MOF material was prepared with a polar organic ligand including a fluorine group. In addition, a polar MOF material can be produced under continuous flow conditions with a space time yield (STY) of 7188 kg m −3 day −1 . Furthermore, a response surface methodology (RSM) was used to optimize the process conditions with the Box–Behnken design. Moreover, the piezoelectric properties of MIL-53(Cr)-F nanocrystals were probed using dual AC resonance tracking piezo-response force microscopy (PFM) and piezoresponse force spectroscopy (PFS). A PFM amplitude of 300–400 pm and a maximum amplitude of 1051 pm in a butterfly loop were observed indicating its piezoelectricity and ferroelectricity. The MIL-53(Cr)-F nanocrystals display second harmonic generation activity, indicating their polar organization. Therefore, MIL-53(Cr) with a polar linker has the potential to be used as a promising piezoelectric material, which can be produced at a large scale by continuous-flow chemistry.